Implementation of Wiretapping Authority by Prosecutors in Corruption Crimes in Central Java: Implementasi Kewenangan Penyadapan oleh Jaksa Dalam Tindak Pidana Korupsi di Jawa Tengah - Heryanto, Diana Marlisye; Sumardiana, Benny (Annual Review of Legal Studies, 2024)
Corruption is a serious threat to the development and welfare of Indonesian society. Wiretapping is one of the powers given to prosecutors to uncover corruption cases. This research aims to analyze the legality of the Prosecutor's authority in conducting wiretapping in corruption cases in Central Java and analyze the implementation of wiretapping authority by the Central Java High Prosecutor's Office. This research uses a qualitative approach with empirical or non-doctrinal research. The research location is the Central Java Prosecutor's Legal Area. Data collection was carried out by observation and interviews, as well as using an interaction data analysis model. The research results show that the prosecutor has the legal authority to conduct wiretapping in cases of criminal acts of corruption in Central Java. This authority is based on Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia and the Criminal Procedure Code (KUHAP). However, the implementation of wiretapping must comply with established procedures and limits. The Central Java High Prosecutor's Office has implemented wiretapping authority in handling around 10 corruption cases in the last two years. Wiretapping procedures include applying for permission, limiting the subject and time of wiretapping, making an official report, and using the results of wiretapping as evidence in court. The obstacles faced include limited human and technological resources and maintaining the security of wiretapping results.